40 The first irish minimally invasive mitral repair cases. (28th September 2016) - Tolan, M
Abstract : The first five minimally invasive mitral surgery cases are reported. Age range was 69 to 76 years, two ladies and three men; all had degenerative mitral regurgitation and all valves were repaired using standard Carpentier principles. All were performed through a 5 to 8 cm skin incision, right anterolateral thoracotomy and cardiopulmonary bypass established via the femoral vessels. All patients were discharged within 6 days. No patient had residual mitral regurgitation on discharge and there was no morbidity of note in any of the patients. Minimally invasive surgery is a safe alternative to conventional open surgery when performed by an experienced mitral surgeon with appropriate training in minimal techniques.